2021
DOI: 10.3389/fcell.2021.789517
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Ferroptosis in Lung Diseases

Abstract: Ferroptosis is a new form of programmed cell death due to iron-dependent excess accumulation of lipid peroxides and differs from other programmed cell deaths in morphological and biochemical characteristics. The process of ferroptosis is precisely regulated by iron metabolism, lipid metabolism, amino acid metabolism, and numerous signaling pathways, and plays a complex role in many pathophysiological processes. Recent studies have found that ferroptosis is closely associated with the development and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 95 publications
1
41
0
Order By: Relevance
“…Of note, ferroptosis, which denotes an iron-dependent, nonapoptotic mode of cell death characterized by an accumulation of lipid ROS at the cell membrane, was observed in several lung diseases, such as lung cancer. In addition, the generation of oxidative stress as a result of SSAT overexpression, induced lipid peroxidation, and cell death have also been reported in several studies [ 8 , 9 , 26 , 28 ].…”
Section: Involvement Of Ssat In Cellular Mechanismsmentioning
confidence: 84%
“…Of note, ferroptosis, which denotes an iron-dependent, nonapoptotic mode of cell death characterized by an accumulation of lipid ROS at the cell membrane, was observed in several lung diseases, such as lung cancer. In addition, the generation of oxidative stress as a result of SSAT overexpression, induced lipid peroxidation, and cell death have also been reported in several studies [ 8 , 9 , 26 , 28 ].…”
Section: Involvement Of Ssat In Cellular Mechanismsmentioning
confidence: 84%
“…With the progress of ferroptosis-related research, it has been revealed that ferroptosis plays a crucial role in many pathological changes in lung diseases. Among these findings, the dysregulation of ferroptosis in lung cancer has been more widely and deeply explored (Xu et al, 2021b;Yu et al, 2021). In this review, we provide a current understanding and views of ferroptosis in lung diseases, especially beyond lung cancer, from the aspects of the molecular basis and the corresponding therapeutic significance.…”
Section: Discussionmentioning
confidence: 95%
“…Such an example would be Artemisia-derived drugs, used to treat malaria and considered in treating SARS-CoV-2 infected patients. Artesunate can increase the lysosomal degradation of intracellular ferritin with the release of free iron and oxidative stress, leading to the death of the infected cells (therapeutic induction of ferroptosis) [6,79,80]. Therefore, there is a clear need for more research to enable knowledge on the exact link between preexisting patient comorbidities, serum ferritin levels, and COVID-19.…”
Section: Future Perspectivesmentioning
confidence: 99%